Elaboração e validação de um instrumento de avaliação do nível de consciência lingüística - Raymundo, Valéria Pinheiro (2006)
The objective of this research was to elaborate and validate an instrument of linguistic consciousness levei evaluation of adult learners of English, native speakers of Portuguese. ln arder to reach this goal, ten instruments were elaborated, focusing on right and wrong forms of simple sentences in different tenses and aspects distributed in two groups: interlingual and intralingual errors. Content, construct and criterion-related validity were accomplished according to a stipulated script of procedures. The tests were applied in a sample composed by students from General English, Languages and Aeronautical Science courses of PUCRS between 2004 and 2005. The examination of the validity of this type of instrument showed that it is possible to construct a reliable test based on leveis of linguistic consciousness defined as pre-consciousness 1, pre consciousness 2, consciousness and full consciousness from the judgment, identification, correction and/or explanation of the errar. Through lhe ana\ysis of comp\ementary questions, it was possib\e to observe lhe existence of significant difference between the subjects of the feminine group and the masculine group consciousness leveis. A significant relation between consciousness levei and performance of lhe subjects from General English and Languages courses was also observed. The interpretation of lhe data obtained through lhe validated instrument provided a possible c\assification of the subjects in over-users, under-users and optimal users of lhe monitor and a reorganization of the students from the different courses.